2022
DOI: 10.1126/sciadv.abq0117
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial pyruvate supports lymphoma proliferation by fueling a glutamate pyruvate transaminase 2–dependent glutaminolysis pathway

Abstract: The fate of pyruvate is a defining feature in many cell types. One major fate is mitochondrial entry via the mitochondrial pyruvate carrier (MPC). We found that diffuse large B cell lymphomas (DLBCLs) consume mitochondrial pyruvate via glutamate-pyruvate transaminase 2 to enable α-ketoglutarate production as part of glutaminolysis. This led us to discover that glutamine exceeds pyruvate as a carbon source for the tricarboxylic acid cycle in DLBCLs. As a result, MPC inhibition led to decreased glutaminolysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…Glutamate conversion to AKG can conventionally occur via three mitochondrial enzymes: GDH, which consumes glutamate and NAD +to generate AKG, NADH, and ammonia; GOT2, which converts glutamate and OAA to aspartate and AKG; and GPT2, which converts glutamate and pyruvate to AKG and alanine. The requirement for MPC1 to maintain AKG levels suggests that pyruvate-dependent GPT2 activity is a dominant route for AKG production in these cells, consistent with recent studies ( Figure 5—figure supplement 1A ; Rossiter et al, 2021 ; Wei et al, 2022 ; Weinberg et al, 2010 ). Indeed, MPC1 KO was also associated with a decrease in alanine levels, corroborating studies that identify GPT2 as a dominant source of alanine production ( Figure 5—figure supplement 1B ; Rossiter et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
“…Glutamate conversion to AKG can conventionally occur via three mitochondrial enzymes: GDH, which consumes glutamate and NAD +to generate AKG, NADH, and ammonia; GOT2, which converts glutamate and OAA to aspartate and AKG; and GPT2, which converts glutamate and pyruvate to AKG and alanine. The requirement for MPC1 to maintain AKG levels suggests that pyruvate-dependent GPT2 activity is a dominant route for AKG production in these cells, consistent with recent studies ( Figure 5—figure supplement 1A ; Rossiter et al, 2021 ; Wei et al, 2022 ; Weinberg et al, 2010 ). Indeed, MPC1 KO was also associated with a decrease in alanine levels, corroborating studies that identify GPT2 as a dominant source of alanine production ( Figure 5—figure supplement 1B ; Rossiter et al, 2021 ).…”
Section: Resultssupporting
confidence: 89%
“…In addition, with increasing age, chondrocyte proliferation decreased, and mitochondrial senescence and dysfunction emerged, thereby increasing ROS production and the levels of fatty acids, glucose, and inflammation mediators and, eventually, cartilage damage [ 46 ]. α-KG is an essential metabolite of the mitochondrial TCA cycle that can regulate mitochondrial metabolism, antioxidation, and anti-inflammation [ [14] , [15] , [16] , [17] ], and its serum levels gradually decrease with age [ 30 ]. Accordingly, in the present study, we first quantified α-KG content in cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The tricarboxylic acid (TCA) cycle, also known as citric acid or Krebs cycle, occurs in the mitochondria in eukaryotes and regulates mitochondrial function and oxidative stress [ [14] , [15] , [16] , [17] ]. α-ketoglutarate (α-KG) is a key intermediate metabolite in the TCA cycle, also known as 2-oxoglutarate [ 18 ], which contributes to a variety of metabolic processes, including the biogenesis of numerous amino acids, nucleotide, lipid, and carnitine biosynthesis, and as a cofactor in numerous dioxygenases [ [19] , [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study identified that an oxidative mitochondrial NAD + /NADH ratio was critical in ovarian cancer (42), and another reported that high SLC25A51 levels in hepatocellular carcinoma (HCC) promoted cancer progression through SIRT5 activation (43). Additionally, there are some phenotypic similarities between SLC25A51 loss in AML and block of mitochondrial pyruvate carrier in oxidative Non-Hodgkin Diffuse Large B Cell Lymphomas (44). It is possible that these carriers may function together to promote oxidative TCA flux in this blood cancer as well.…”
Section: Discussionmentioning
confidence: 99%